2020
DOI: 10.1186/s12968-020-0600-1
|View full text |Cite
|
Sign up to set email alerts
|

Sub-segmental quantification of single (stress)-pass perfusion CMR improves the diagnostic accuracy for detection of obstructive coronary artery disease

Abstract: Background Myocardial perfusion with cardiovascular magnetic resonance (CMR) imaging is an established diagnostic test for evaluation of myocardial ischaemia. For quantification purposes, the 16 segment American Heart Association (AHA) model poses limitations in terms of extracting relevant information on the extent/severity of ischaemia as perfusion deficits will not always fall within an individual segment, which reduces its diagnostic value, and makes an accurate assessment of outcome data or a result compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The subdividing of myocardial segments into both epicardial and endocardial layers, along with an additional circumferential subdivision resulting in an analysis of 96 segments, as opposed to the conventional 16-segment American Heart Association model, has demonstrated encouraging results in the context of the stress-LGE approach. This expanded segment analysis holds promise as it theoretically diminishes the likelihood of encountering segments exhibiting partial abnormalities in perfusion defects and LGE 10 and may represent an improvement to the prosed stress-LGE approach.…”
Section: See Article By Swoboda Et Almentioning
confidence: 99%
“…The subdividing of myocardial segments into both epicardial and endocardial layers, along with an additional circumferential subdivision resulting in an analysis of 96 segments, as opposed to the conventional 16-segment American Heart Association model, has demonstrated encouraging results in the context of the stress-LGE approach. This expanded segment analysis holds promise as it theoretically diminishes the likelihood of encountering segments exhibiting partial abnormalities in perfusion defects and LGE 10 and may represent an improvement to the prosed stress-LGE approach.…”
Section: See Article By Swoboda Et Almentioning
confidence: 99%
“…These techniques are promising, and based on a recent meta-analysis, they achieve sensitivity, specificity and area under the curve of 0.77, 0.84, and 0.87, respectively, for the semiquantitative analysis and 0.77, 0.86 and 0.88, respectively, for the quantitative analysis. Overall, semiquantitative, quantitative stress-CMR perfusion and subsegmental qualitative analyses are a new application for assessing ischemic burden and coronary microvascular function; however, standardization and validation of those techniques are still ongoing and are required before they can be safely used in clinical practice [40][41][42].…”
Section: Stress Cardiac Magnetic Resonancementioning
confidence: 99%
“…Data evidenced how an ischemia burden involving ≥1.5 ischemic segments was the strongest predictor of hard clinical events, and the authors concluded that patients with zero or 1 ischemic segment could be safely deferred to revascularization [ 57 ]. Concerning the ischemia extent, a technical advantage of S-CMR over SPECT relies on its higher spatial resolution (3 mm × 3 mm vs. 10 mm × 10 mm in-plane spatial resolution), which allows recording of smaller myocardial areas of hypoperfusion resulting in an even better diagnostic performance [ 58 ].…”
Section: Prognostic Role Of Stress Cmrmentioning
confidence: 99%